2017
DOI: 10.5539/ijms.v9n1p109
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Foreign Investor Trading Activity on Vietnamese Stock Market

Abstract: The Literature Review Financial Liberalization and Stock Market DevelopmentFinancial liberalization plays an important role on developing equity market in emerging countries. Henry (2000) conducts the research on the sample of 12 emerging markets and gives and strong evidence to prove that equity index witnesses the significant abnormal return after government opens capital market. By using some control variables like world stock return, macroeconomic factors and concurrent economic reforms, this paper sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The phenomenon of foreign investors in the capital market is a global phenomenon. Rhee & Wang (2009), Ding et al, (2013), Lee & Chung, (2015); Nguyen et al, (2017) Lee & Chung, found that foreign investors had a positive effect on Amihud Illiquidity, but had a negative effect on bid-ask spreads. Nguyen et al (2017) show that foreign investors negatively affect liquidity on the Vietnamese Stock Market.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The phenomenon of foreign investors in the capital market is a global phenomenon. Rhee & Wang (2009), Ding et al, (2013), Lee & Chung, (2015); Nguyen et al, (2017) Lee & Chung, found that foreign investors had a positive effect on Amihud Illiquidity, but had a negative effect on bid-ask spreads. Nguyen et al (2017) show that foreign investors negatively affect liquidity on the Vietnamese Stock Market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rhee & Wang (2009), Ding et al, (2013), Lee & Chung, (2015); Nguyen et al, (2017) Lee & Chung, found that foreign investors had a positive effect on Amihud Illiquidity, but had a negative effect on bid-ask spreads. Nguyen et al (2017) show that foreign investors negatively affect liquidity on the Vietnamese Stock Market. Thanatawee also found that foreign investors negatively affected liquidity.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their low proportions of the trading volume and tendency towards the net purchase, as shown in Figure 2, also support this strategy. Also, their trading activities tend to become the pattern for domestic investors (Nguyen, 2017). These findings also contribute to explaining the stability of stock prices from a trading perspective.…”
Section: The Impact Of Foreign Ownership On Stock Return Volatility Imentioning
confidence: 67%
“…Another study by Vo (2016b) adds that foreign investors in the Vietnam stock market focus on long-run perspectives rather than short-term gain by investigating the impact of foreign ownership on the corporate risk-taking activity for a sample of 263 Vietnamese listed companies in the 2007-2014 period. In other words, they pursue an inactive buy-and-hold investment strategy, which reduces the need for frequent trading for price discovery (Batten & Vo, 2015;Nguyen, 2017). Their low proportions of the trading volume and tendency towards the net purchase, as shown in Figure 2, also support this strategy.…”
Section: The Impact Of Foreign Ownership On Stock Return Volatility Imentioning
confidence: 96%
“…Multiple researchers have conducted studies that are relevant to this study. , Nguyen (2017), and Samarakoon (2009) found that foreign investor trading activity caused a bi-directional impact on the stock market return, while Junior and Eid (2017) showed that the impact doubled during a crisis. Peranginangin et al (2016); Agudelo (2010); and Liew, Lim, and Goh (2018) DOI 10.1201/9781003196013-2 observed that trading inactivity reduced liquidity, and its impact was greater during a crisis.…”
Section: Literature Reviewmentioning
confidence: 99%